2023
DOI: 10.3389/fimmu.2023.1193053
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microglia in adult hippocampal neurogenesis in depression and their therapeutics

Shaoyi Fang,
Zhibin Wu,
Yali Guo
et al.

Abstract: Adult hippocampal neurogenesis generates functional neurons from neural progenitor cells in the hippocampal dentate gyrus (DG) to complement and repair neurons and neural circuits, thus benefiting the treatment of depression. Increasing evidence has shown that aberrant microglial activity can disrupt the appropriate formation and development of functional properties of neurogenesis, which will play a crucial role in the occurrence and development of depression. However, the mechanisms of the crosstalk between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 271 publications
0
6
0
Order By: Relevance
“…Subsequently, the expression of phenotype and functional markers of microglia in AMD neuroretina was investigated. The results showed that inflammatory cytokines (including IL1B, IL6, and TNF) ( Fang et al, 2023 ), microglial phagocytic markers (CTSB, GRN, and C1QA) ( De Schepper et al, 2023 ), cell migration signatures (FAK, RAC1, and CDC42) ( Rosmus et al, 2022 ), and classic disease-associated microglia (DAM) markers (IBA1, CST3, HEXB, APOE, and TREM2) ( Deczkowska et al, 2018 ) were upregulated in microglia, while the anti-inflammatory cytokines (IL10 and TGFB) ( Fang et al, 2023 ) were at low expression levels in microglia ( Figure 5A ). Pathway enrichment analysis was then performed and the mainly upregulated pathways in microglia of AMD neuroretina included phagocytosis-related pathways (Phagosome, Microglia phagocytosis pathway, Synapse pruning, Regulation of cell killing, and Positive regulation of neuron death), complete activation-associated pathways (C1q complex and Complete activation), inflammation-related pathways (IL-18 signaling pathway and Regulation of inflammatory response) and Regulation of chemotaxis pathway ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the expression of phenotype and functional markers of microglia in AMD neuroretina was investigated. The results showed that inflammatory cytokines (including IL1B, IL6, and TNF) ( Fang et al, 2023 ), microglial phagocytic markers (CTSB, GRN, and C1QA) ( De Schepper et al, 2023 ), cell migration signatures (FAK, RAC1, and CDC42) ( Rosmus et al, 2022 ), and classic disease-associated microglia (DAM) markers (IBA1, CST3, HEXB, APOE, and TREM2) ( Deczkowska et al, 2018 ) were upregulated in microglia, while the anti-inflammatory cytokines (IL10 and TGFB) ( Fang et al, 2023 ) were at low expression levels in microglia ( Figure 5A ). Pathway enrichment analysis was then performed and the mainly upregulated pathways in microglia of AMD neuroretina included phagocytosis-related pathways (Phagosome, Microglia phagocytosis pathway, Synapse pruning, Regulation of cell killing, and Positive regulation of neuron death), complete activation-associated pathways (C1q complex and Complete activation), inflammation-related pathways (IL-18 signaling pathway and Regulation of inflammatory response) and Regulation of chemotaxis pathway ( Figure 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…The crucial role of hippocampal BDNF in mood regulation has been amply documented [18][19][20][21][22]. Thus, it has been confirmed that dysregulation or impairment in BDNF could precipitate MDD 3 [23] [24]. Conversely, BDNF injection directly into the hippocampus imparts an antidepressant effect, and up-regulation of BDNF is often associated with an anti-depressant response [25].…”
Section: Neurotrophic Factors and Mddmentioning
confidence: 99%
“…At stage 4, the mature neurons establish synaptic connections via their dendrites and axons, with other neurons and glial cells, ensuring normal CNS functioning [27]. Indeed, newly born neurons in the DG of the adult brain contribute to the cognitive and emotional functions of the hippocampus [23][24] [28].…”
Section: Neurotrophic Factors and Mddmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroglial cells play a significant role in the normal physiological processes of the central nervous system, including synaptic transmission, neural plasticity, regulation of neurons, and the local microenvironment ( Fang et al, 2023 ). Microglial cells are the resident immune cells of the CNS, constituting approximately 5%–10% of CNS cells in mice and 0.5%–16.6% in human CNS cells.…”
Section: The Antidepressant Mechanisms Of Cssmentioning
confidence: 99%